Ottoman imperial diplomacy : a political, social and cultural history - Gurpinar, Dogan (London : I.B. Tauris, 2014)
The Ottoman Empire maintained a complex and powerful bureaucratic system which enforced the Sultan's authority across the imperial territories. This bureaucracy continued to gain in power and prestige, even as the empire itself began to crumble at the end of the nineteenth century. Through extensive new research in the Ottoman archives, Dogan Grupinar assesses the intellectual, cultural and ideological foundations of the diplomatic service under Sultan Abdulhamid II. Ottoman Imperial Diplomacy presents a new model for understanding the formation of the modern Turkish nation, arguing that the Hamidian imperial bureaucracy and the ethos this bureaucracy fostered - was constitutive in the emergence of Turkish nationalism. This book will be essential reading for historians of the Ottoman Empire and for those seeking to understand the history of Modern Turkey. -- Publisher.
Includes bibliographical references (page: [267]-345) and index.
Keywords: Civil service -- Turkey -- History -- 19th century; Bureaucracy -- Turkey -- History -- 19th century; Diplomatic and consular service, Turkish -- History -- 19th century; Turkey -- Foreign relations -- 19th century; Turkey -- History -- Ottoman Empire, 1288-1918.